2013
DOI: 10.1073/pnas.1300624110
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the replisome following arrest by UV-induced DNA damage in Escherichia coli

Abstract: Accurate replication in the presence of DNA damage is essential to genome stability and viability in all cells. In Escherichia coli, DNA replication forks blocked by UV-induced damage undergo a partial resection and RecF-catalyzed regression before synthesis resumes. These processing events generate distinct structural intermediates on the DNA that can be visualized in vivo using 2D agarose gels. However, the fate and behavior of the stalled replisome remains a central uncharacterized question. Here, we use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Another approach to tolerate CPD involves polymerases transiently dissociating upon encountering this lesion and allowing repair enzymes or translesion polymerases to repair or bypass this lesion. The helicase-primase complex remains bound to the template DNA and serves to maintain the integrity of the replication fork, directing the reassembled replisome to the correct location [87]. …”
Section: Bypassing Dna Damage By the Dna Replisomementioning
confidence: 99%
“…Another approach to tolerate CPD involves polymerases transiently dissociating upon encountering this lesion and allowing repair enzymes or translesion polymerases to repair or bypass this lesion. The helicase-primase complex remains bound to the template DNA and serves to maintain the integrity of the replication fork, directing the reassembled replisome to the correct location [87]. …”
Section: Bypassing Dna Damage By the Dna Replisomementioning
confidence: 99%
“…However, multiple studies have shown empirically that recBC mutants remain able to restore replication after these challenges, and a series of studies have shown directly that RecBCD plays no role in the degradation of the nascent fork DNA at impeded replication forks [62, 106109]. In addition, the use of 2D-agarose gels to examine arrested forks at a range of impediments in both prokaryotes and eukaryotes has shown that the replication fork DNA remains stable and intact throughout the recovery process [110115]. Thus, despite its persistence in the literature [116–122], there is little experimental support to suggest that fork collapse occurs frequently or is a substrate for recBCD processing.…”
Section: Double-strand Breaks May Be Infrequent Eventsmentioning
confidence: 99%
“…[1] The E. coli replisome transiently stalls at leading-strand template lesionsa nd can either reinitiate replication downstream of the lesion with the aid of the primase DnaG or recruit special DNA polymerases thatc an bypass the lesion through translesion synthesis. [37] DNA polymerase IV could engage productively with the E. coli replisome to bypass leading-strand templateb ulky lesionsi ncluding CPD and THF. [38] Polymerases transiently dissociate from the DNA template upon encountering the CPD lesion.T he helicase and primase complex bound to the template DNA maintains the polymerase at the replication fork.…”
Section: Resultsmentioning
confidence: 99%